# Welcome back

## Find a book, put up your feet, stay awhile

Sign in with Facebook

Sorry, we are unable to log you in via Facebook at this time. Please try again later.

or

Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more

Download

Standard view

Full view

of .

Look up keyword

Like this

Share on social networks

0Activity

×

0 of .

Results for: No results containing your search query

P. 1

Form 1Ratings: (0)|Views: 0|Likes: 0

Published by Nithin Janardhanan

See more

See less

https://www.scribd.com/doc/94127263/Form-1

05/19/2012

text

original

MATHEMATICAL FORMULAEAlgebra

1. (

a

+

b

)

2

=

a

2

+ 2

ab

+

b

2

;

a

2

+

b

2

= (

a

+

b

)

2

−

2

ab

2. (

a

−

b

)

2

=

a

2

−

2

ab

+

b

2

;

a

2

+

b

2

= (

a

−

b

)

2

+ 2

ab

3. (

a

+

b

+

c

)

2

=

a

2

+

b

2

+

c

2

+ 2(

ab

+

bc

+

ca

)4. (

a

+

b

)

3

=

a

3

+

b

3

+ 3

ab

(

a

+

b

);

a

3

+

b

3

= (

a

+

b

)

3

−

3

ab

(

a

+

b

)5. (

a

−

b

)

3

=

a

3

−

b

3

−

3

ab

(

a

−

b

);

a

3

−

b

3

= (

a

−

b

)

3

+ 3

ab

(

a

−

b

)6.

a

2

−

b

2

= (

a

+

b

)(

a

−

b

)7.

a

3

−

b

3

= (

a

−

b

)(

a

2

+

ab

+

b

2

)8.

a

3

+

b

3

= (

a

+

b

)(

a

2

−

ab

+

b

2

)9.

a

n

−

b

n

= (

a

−

b

)(

a

n

−

1

+

a

n

−

2

b

+

a

n

−

3

b

2

+

···

+

b

n

−

1

)10.

a

n

=

a.a.a...n

times11.

a

m

.a

n

=

a

m

+

n

12.

a

m

a

n

=

a

m

−

n

if

m > n

= 1 if

m

=

n

=1

a

n

−

m

if

m < n

;

a

∈

R,a

= 013. (

a

m

)

n

=

a

mn

= (

a

n

)

m

14. (

ab

)

n

=

a

n

.b

n

15.

ab

n

=

a

n

b

n

16.

a

0

= 1 where

a

∈

R,a

= 017.

a

−

n

=1

a

n

,a

n

=1

a

−

n

18.

a

p/q

=

q

√

a

p

19. If

a

m

=

a

n

and

a

=

±

1

,a

= 0 then

m

=

n

20. If

a

n

=

b

n

where

n

= 0, then

a

=

±

b

21. If

√

x,

√

y

are quadratic surds and if

a

+

√

x

=

√

y

, then

a

= 0 and

x

=

y

22. If

√

x,

√

y

are quadratic surds and if

a

+

√

x

=

b

+

√

y

then

a

=

b

and

x

=

y

23. If

a,m,n

are positivereal numbersand

a

= 1, then log

a

mn

= log

a

m

+log

a

n

24. If

a,m,n

are positive real numbers,

a

= 1, then log

a

mn

= log

a

m

−

log

a

n

25. If

a

and

m

are positive real numbers,

a

= 1 then log

a

m

n

=

n

log

a

m

26. If

a,b

and

k

are positive real numbers,

b

= 1

,k

= 1, then log

b

a

=log

k

a

log

k

b

27. log

b

a

=1log

a

b

where

a,b

are positive real numbers,

a

= 1

,b

= 128. if

a,m,n

are positive real numbers,

a

= 1 and if log

a

m

= log

a

n

, then

m

=

n

Typeset by

AMS

-TEX

2

29. if

a

+

ib

= 0 where

i

=

√−

1, then

a

=

b

= 030. if

a

+

ib

=

x

+

iy

, where

i

=

√−

1, then

a

=

x

and

b

=

y

31. The roots of the quadratic equation

ax

2

+

bx

+

c

= 0;

a

= 0 are

−

b

±√

b

2

−

4

ac

2

a

The solution set of the equation is

−

b

+

√

∆2

a,

−

b

−√

∆2

a

where ∆ = discriminant =

b

2

−

4

ac

32. The roots are real and distinct if ∆

>

0.33. The roots are real and coincident if ∆ = 0.34. The roots are non-real if ∆

<

0.35. If

α

and

β

are the roots of the equation

ax

2

+

bx

+

c

= 0

,a

= 0 theni)

α

+

β

=

−

ba

=

−

coeﬀ. of

x

coeﬀ. of

x

2

ii)

α

·

β

=

ca

=constant termcoeﬀ. of

x

2

36. The quadratic equation whose roots are

α

and

β

is (

x

−

α

)(

x

−

β

) = 0i.e.

x

2

−

(

α

+

β

)

x

+

αβ

= 0i.e.

x

2

−

Sx

+

P

= 0 where

S

=Sum of the roots and

P

=Product of theroots.37. For an arithmetic progression (A.P.) whose ﬁrst term is (

a

) and the commondiﬀerence is (

d

).i)

n

th

term=

t

n

=

a

+ (

n

−

1)

d

ii) The sum of the ﬁrst (

n

) terms =

S

n

=

n

2(

a

+

l

) =

n

2

{

2

a

+ (

n

−

1)

d

}

where

l

=last term=

a

+ (

n

−

1)

d

.38. For a geometric progression (G.P.) whose ﬁrst term is (

a

) and common ratiois (

γ

),i)

n

th

term=

t

n

=

aγ

n

−

1

.ii) The sum of the ﬁrst (

n

) terms:

S

n

=

a

(1

−

γ

n

)1

−

γ

if

γ <

1=

a

(

γ

n

−

1)

γ

−

1if

γ >

1=

na

if

γ

= 1

.

39. For any sequence

{

t

n

}

,S

n

−

S

n

−

1

=

t

n

where

S

n

=Sum of the ﬁrst (

n

)terms.40.

n

γ

=1

γ

= 1 + 2 + 3 +

···

+

n

=

n

2(

n

+ 1).41.

n

γ

=1

γ

2

= 1

2

+ 2

2

+ 3

2

+

···

+

n

2

=

n

6(

n

+ 1)(2

n

+ 1).

- Read and print without ads
- Download to keep your version
- Edit, email or read offline

© Copyright 2015 Scribd Inc.

Language:

Choose the language in which you want to experience Scribd:

Sign in with Facebook

Sorry, we are unable to log you in via Facebook at this time. Please try again later.

or

Password Reset Email Sent

Sign up with Facebook

Sorry, we are unable to log you in via Facebook at this time. Please try again later.

or

By joining, you agree to our

read free for one month

Personalized recommendationsbased on books you love

Syncing across all your devices

Join with Facebook

or Join with EmailSorry, we are unable to log you in via Facebook at this time. Please try again later.

Already a member? Sign in.

By joining, you agree to our

to download

Personalized recommendationsbased on books you love

Syncing across all your devices

Continue with Facebook

Sign inJoin with emailSorry, we are unable to log you in via Facebook at this time. Please try again later.

By joining, you agree to our

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

CANCEL

OK

You've been reading!

NO, THANKS

OK

scribd